Effects of the marine biotoxins Okadaic acid and Dinophysistoxins on fish - Corriere, Mauro (2021)
Natural high proliferations of toxin-producing microorganisms in marine and freshwater environments result in dreadful consequences at the socioeconomically and environmental level due to water and seafood contamination. Monitoring programs and scientific evidence point to harmful algal blooms (HABs) increasing in frequency and intensity as a result of global climate alterations. Among marine toxins, the okadaic acid (OA) and the related dinophysistoxins (DTX) are the most frequently reported in EU waters, mainly in shellfish species. These toxins are responsible for human syndrome diarrhetic shellfish poisoning (DSP). Fish, like other marine species, are also exposed to HABs and their toxins. However, reduced attention has been given to exposure, accumulation, and effects on fish of DSP toxins, such as OA. The present review intends to summarize the current knowledge of the impact of DSP toxins and to identify the main issues needing further research. From data reviewed in this work, it is clear that exposure of fish to DSP toxins causes a range of negative effects, from behavioral and morphological alterations to death. However, there is still much to be investigated about the ecological and food safety risks related to contamination of fish with DSP toxins.